Uniform Metal-assisted Chemical Etching and the Stability of Catalysts. Issue 1801 (2015) - Li, Liyi; Holmes, Colin M.; Hah, Jinho; Hildreth, Owen J.; Wong, Ching P.
ABSTRACT: Recently, metal-assisted chemical etching (MaCE) has been demonstrated as a promising technology in fabrication of uniform high-aspect-ratio (HAR) micro- and nanostructures on silicon substrates. In this work, MaCE experiments on 2 μm-wide line patterns were conducted using Au or Ag as catalysts. The performance of the two catalysts show sharp contrast. In MaCE with Au, a HAR trench was formed with uniform geometry and vertical sidewall. In MaCE with Ag, shallow and tapered etching profiles were observed, which resembled the results from isotropic etching. The sidewall tapering phenomena can be explained by the dissolution and re-deposition of the Ag catalyst in the etchant solution. The existence of Ag that was redeposited on the sidewall was further confirmed by energy dispersive spectrum. Also, etchant composition is found to play a profound role in influencing the etching profile by the Ag catalysts.